2016
DOI: 10.1177/0333102415625614
|View full text |Cite
|
Sign up to set email alerts
|

Migraine biomarkers in cerebrospinal fluid: A systematic review and meta-analysis

Abstract: Objective: To perform a meta-analysis of migraine biomarkers in cerebrospinal fluid (CSF) and of corresponding blood concentrations. Methods: We conducted a systematic search for studies that measured biochemical compounds in CSF of chronic or episodic migraineurs and non-headache controls. Subsequent searches retrieved studies with blood measurements of selected CSF biomarkers. If a compound was assessed in three or more studies, results were pooled in a meta-analysis with standardised mean differences (SMD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
108
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 96 publications
1
108
1
Order By: Relevance
“…Lending support to this notion are findings that serum levels of CGRP obtained from the external jugular vein are elevated in patients during migraine (with and without aura) [7, 11, 12]. In addition, increased CGRP levels have been reported in saliva and cerebrospinal fluid during migraine attacks [13, 14]. Further evidence of the involvement of CGRP in migraine is provided by data from clinical trials, in which triptans, acute anti-migraine drugs that block CGRP release [15, 16], and molecules that block activity of CGRP or its receptor could effectively alleviate headache pain [17].…”
Section: Introductionmentioning
confidence: 93%
“…Lending support to this notion are findings that serum levels of CGRP obtained from the external jugular vein are elevated in patients during migraine (with and without aura) [7, 11, 12]. In addition, increased CGRP levels have been reported in saliva and cerebrospinal fluid during migraine attacks [13, 14]. Further evidence of the involvement of CGRP in migraine is provided by data from clinical trials, in which triptans, acute anti-migraine drugs that block CGRP release [15, 16], and molecules that block activity of CGRP or its receptor could effectively alleviate headache pain [17].…”
Section: Introductionmentioning
confidence: 93%
“…A recent systematic review and meta-analysis of migraine biomarkers has shown that CGRP in CSF and blood was elevated in chronic migraine patients (glutamate and NGF were also increased), and levels of the endogenous opiate ÎČ-endorphin decreased. 135 Preclinically, it has been shown that cortical spreading depolarization/depression (CSD) may trigger the release of neuropeptides such as CGRP 136 into the jugular vein and CSF from the primary trigeminal afferent fibers, 137 where it could promote sensitization of the trigeminal system. In contrast, there are findings 138 that suggest that acute activation of CGRP receptors may not play a key role in mediating CSD-evoked headache, but CGRP-mediated activation of meningeal afferents evoked by cortical efflux of potassium ion could promote headache.…”
Section: Where Does Cgrp Come From To Trigger a Migraine Attack?mentioning
confidence: 99%
“…Several lines of evidence support a central role of CGRP in migraine pathology [26–28]. Plasma CGRP levels, as well as CGRP cerebrospinal fluid levels, are increased during a migraine attack [18].…”
Section: Discussionmentioning
confidence: 99%